Keputusan Pemerintah Amerika Serikat Melakukan Pengeboran Minyak di Perairan Arktik Kutub Utara - Fara Wahyu, Oktariani (2019)
This study discusses the background that influenced the United States in its decision regarding oil drilling in Arctic waters, the Arctic, which was carried out in 2012 to 2015. This decision began when the Arctic region was suspected of having promising potential oil, gas and natural gas reserves. In the context of the American government related to oil drilling in Arctic waters it can be said to be an attempt by the United States in securing energy. The availability concept is an important aspect in expanding United States oil production. In addition, dependence on foreign energy is one of the factors that can also affect the energy security of the United States. The Arctic region is considered as the next logical place for the United States to be used as a region for further development of new oil supplies. The prospect of this exploration activity can provide benefits for the United States given the large oil content contained in Arctic waters. Keywords: Energy Security, Dependency, Energy Diversification